Characterization of Microbiota in Endometrial Fluid and Vaginal Secretions in Infertile Women with Repeated Implantation Failure. (21st May 2019) - Kitaya, Kotaro; Nagai, Yoko; Arai, Wataru; Sakuraba, Yoshiyuki; Ishikawa, Tomomoto
Abstract : Studies suggest that persisting intrauterine bacterial infectious conditions such as chronic endometritis potentially impair the embryo implantation process. The microbial environment in the female reproductive tract, however, remains largely undetermined in infertile patients with a history of repeated implantation failure (RIF). Using next-generation sequencing, we aimed to characterize the microbiota in the endometrial fluid (EF) and vaginal secretions (VS) in women with RIF. Twenty-eight infertile women with a history of RIF and eighteen infertile women undergoing the first in vitro fertilization-embryo transfer attempt (the control group) were enrolled in the study. On days 6-8 in the luteal phase of the natural, oocyte-pickup, or hormone replacement cycle, the paired EF and VS samples were obtained separately. Extracted genomic DNA was pyrosequenced for the V4 region of 16S ribosomal RNA using a next-generation sequencer. The EF microbiota had higher α -diversity and broader bacterial species than the VS microbiota both in the RIF and control groups. The analysis of the UniFrac distance matrices between EF and VS also revealed significantly different clustering. Additionally, the EF microbiota, but not the VS microbiota, showed significant variation in community composition between the RIF group and the control group. Burkholderia species were not detected in the EF microbiota of any samples in the control group but were detectable in a quarter of the RIF group. To our best knowledge, this is the first study investigating the microbiota in the paired EF and VS samples in infertile women with RIF.